PENGARUH IKLIM SEKOLAH DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA SD SWASTA BERYAYASAN BUDDHA SE KOTA TANGERANG - Yohanes Rasul Sudarmaji; Muljadi; Situ Asih (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
THE INFLUENCE OF THE SCHOOL ENVIROMENT AND LEARNING DISCIPLINE TO THE ACHIVEMENT OF ELEMENTARY SCHOOL STUDENTS IN ENTERE BUDDHA FONDATION SCHOOL IN TANGERANG CITY ". Meanwhile, this study aims to examine 1) Is there an effect of School Enviroment on learning achievement, 2) is there an effect of Learning discipline on learning achievement, and 3) is there an effect of School Enviroment and Learning discipline on learning achievement together. This type of research includes quantitative research with conclusions drawn through statistical analysis. The research location is in private junior high schools throughout the city of Tangerang, the population is Class V totaling 171 students, and the research sample totaling 120 students. The data collection technique used a closed questionnaire with a Likert scale. Data analysis techniques include: (1) instrument test, validity and reliability test. (2) Research prerequisite test, consisting of normality and linearity tests. (3) Homogeneity test, 4) Hypothesis test, using multiple regression test, partial regression test, F/simultaneous test and coefficient of determination test. Based on the results of the study: There is a positive and very significant effect between School Enviroment (X1) on Learning Achievement (Y) with a correlation coefficient score of ry1 = 0.678a, the influence of High Learning discipline (X1) will have a strong influence on Learning Achievement (Y) private Elementary School students in the city of Tangerang with a coefficient of determination score of r2y1 = 0.654, a contribution or influence of 65,4%, the remaining 34,6% was contributed by other variables that have a positive relationship with an increase in student achievement (Y) Elementary School in Tangerang City., the effect of School Enviroment (X1) and Learning discipline (X2) together with strong learning achievement (Y) will have a large relationship with learning achievement (Y), with a determination coefficient score of r2y3 = 0.781. Contribution or influence of 34,6%, the remaining 65,4% was contributed by other variables that have a relationship with increasing learning achievement (Y).